Determinants of Local Government Financial Independence: A Literature Review - Sisca Mia Astuti; Fajar Gustiawaty Dewi; Pigo Nauli (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to examine the determinants of local government financial independence in Indonesia by synthesizing empirical evidence from recent studies published between 2021 and 2025. Local government financial independence is a key objective of fiscal decentralization, reflecting the ability of regional governments to finance public services and development activities through locally generated revenue while reducing dependence on central government transfers. This study focuses on five main determinants frequently discussed in the literature, namely local taxes, investment, government size, population, and intergovernmental transfers. A narrative literature review approach is employed to analyze and compare findings from fifteen selected empirical studies that investigate these variables across different regional contexts in Indonesia. The results indicate that local taxes consistently have a positive and significant effect on financial independence, highlighting their importance as a sustainable source of local revenue. Intergovernmental transfers are also found to support financial independence in the short term. In contrast, the effects of investment, government size, and population remain mixed and context-dependent, suggesting the influence of governance quality, demographic structure, and regional characteristics. This study contributes to the literature by providing an integrated understanding of recent findings and identifying research gaps that may guide future empirical research and policy formulation aimed at strengthening local government financial independence.